A Case Study of Intrapreneurship Initiatives in Moroccan Family Businesses - ELABJANI , Abdelaziz; BOUGHDADI , Imane (Revue Internationale des Sciences de Gestion, 2024)
This study explores the role of organizational aspects of intrapreneurship in family businesses in Morocco, focusing on corporate culture, business policies and practices, and organizational structures. The results highlight their importance in fostering intrapreneurship. Through a case study involving five participants, conducted within a family business characterized by a propensity for innovation and strong support for entrepreneurship, the importance of a corporate culture that encourages creativity and risk-taking, policies and practices that foster intrapreneurship, and organizational structures that facilitate collaboration and communication, is highlighted. These results indicate significant implications for Moroccan family businesses wishing to promote intrapreneurship, highlighting the need to put in place policies and practices supporting innovation and fostering a corporate culture valuing creativity and risk-taking.